Analisis Sistem Pengendalian Internal (SPI) Atas Persediaan Di CV Bali IT Solusion - Ni Luh Nadia Pradnyandari; Sang Ayu Putu Arie Indraswarawati; I Wayan Budi Satriya (UNHI Press, 2026)
This study aims to analyze the implementation of the Internal Control System (ICS) for inventory at CV Bali IT Solution and evaluate its compliance with the COSO framework. This research uses a qualitative descriptive method with data collection techniques through interviews, observation, and documentation studies. The results indicate that the implementation of inventory ICS at the company has not been fully effective and does not comply with COSO elements, particularly in three main components. Critical weaknesses were found in control activities due to a lack of segregation of duties between purchasing, receiving, and storage functions, as well as a lack of physical supervision such as CCTV. Furthermore, the information and communication component is considered inadequate due to reliance on error-prone semi-manual recording, while the monitoring function is deemed weak because stock opname is only conducted once a year. This research recommends the implementation of strict separation of duties, the use of integrated digital applications, and an increase in the frequency of periodic stock opname.